2005
DOI: 10.1007/s11606-005-0244-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of colorectal cancer screening among urban African Americans

Abstract: OBJECTIVE: To explore colorectal cancer (CRC) screening knowledge, attitudes, barriers, and preferences among urban African Americans as a prelude to the development of culturally appropriate interventions to improve screening for this group. DESIGN:Qualitative focus group study with assessment of CRC screening preferences.SETTING: Community health center serving low-income African Americans. PARTICIPANTS:Fifty-five self-identified African Americans over 40 years of age. MEASUREMENTS AND MAIN RESULTS:Transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
176
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(195 citation statements)
references
References 41 publications
14
176
2
3
Order By: Relevance
“…Although other published studies that have examined cancer screening have identified these factors as relevant, 23,24 the lack of confirmation in our study does not imply they are not important. Fatalistic beliefs have been clearly identified in the cancer screening literature as reasons why African Americans do not pursue cancer screening.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…Although other published studies that have examined cancer screening have identified these factors as relevant, 23,24 the lack of confirmation in our study does not imply they are not important. Fatalistic beliefs have been clearly identified in the cancer screening literature as reasons why African Americans do not pursue cancer screening.…”
Section: Discussioncontrasting
confidence: 79%
“…This finding is shared in other qualitative studies examining CRC screening. 23,24,29 The reasons for this distrust were not well established in this study or in previous studies. Future research needs to clearly delineate what influences these perceptions.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations